G191(P) Improving Response Rate to the Patient Reported Experience Measures Survey (PREMS) in the National Paediatric Diabetes Audit (NPDA). (27th April 2016) - Banu, M; Mohamed, Z; Randell, T; Sachdev, P; Denvir, L
Abstract : Aims: To improve response rate to the NPDA PREMS questionnaire. Methods: Patients/parents/carers were asked to fill in the questionnaire online while waiting to see the doctor at the diabetes clinic. A medical student facilitated the process and explained the questions, if requested. Results: Data from 75 questionnaires was analysed. The young people filled out 56% of the questionnaires (36% by the mother). Age range was 2–18 years, with 38% in the 15–17 year age group, 53% were male. There was a range of ethnicities with the majority (79%) describing themselves as White British. 61% were on multiple daily insulin injections (MDI). 38% were on insulin pump therapy (CSII). 77% said they were seen within an hour of arriving for their appointment. Families said they had enough time to discuss their concerns with the doctors (87%), nurses (80%), dietitians (69%) and psychological services (45%). 73% said they got responses to telephone calls, emails and texts in a timely manner.. 84% said they could contact the diabetes team during working hours with75% saying that they could get advice from the hospital at all hours. Families said they received enough information about managing: High (99%) and low (100%) blood glucose levels Illness (93%) Carbohydrate counting (93%) Exercise (92%) Future health (81%) Emotional wellbeing (84%) Diabetes at school/nursery (92%) CSII (76%) Glucose monitoring (72%) Bolus advisor blood glucose metres (79%) 100% were able to understand the written information. 79% felt they received appropriate dietary advice. 95% felt their religious beliefs were respected. 43% were offered an interpreter and 97% would recommend this clinic to others. Conclusions: Response rate was dramatically improved (75/90 in 3 months compared to previous NPDA PREMS 84/180 in 6 months) by the presence of a facilitator and electronic completion of the questionnaire at clinic. Overall families were satisfied with the care they received from the paediatric diabetes team at Nottingham Children's Hospital.. Areas of the service which appear to require further analysis of feedback and possible improvements are access to psychological support, access to dietetic advice and information on technologies.